Employing AI Technologies in Drafting Public–Private Partnership Contracts in the Field of Healthcare Improvement - Al Adwan, Majed (Qubahan Academic Journal, 2026)
Sustainable development within a nation focuses on improving all governmental facilities within the nation as fully as possible. One of the sectors that has experienced positive development is the health sector. It focuses on optimizing the facilities and patient care services to meet public health needs. At the same time, global legislative developments have accelerated the use of Artificial Intelligence (AI) and its integration into the design, implementation, and supervision of public-private partnership (PPP) contracts to enhance healthcare delivery through a strong legal-health governance framework. This study develops a doctrinal-comparative analysis concerning the legality of using AI technologies for the drafting, execution, and management of PPP contracts within the healthcare sector. More specifically, this study analyses the legal ramifications of the incorporation of AI into healthcare PPPs and intends to lay the foundation for the development of an administrative legal framework concerning the practice. The study aims to assess the administrative legality of the practice in terms of accountability, transparency, and protection of the public interest concerning patient safety, data protection, compliance, and regulation. Ultimately, the study aims to support the efficient operation of public healthcare facilities and the proper and legal use of AI in medical partnership contracts. The study seeks to examine the legal boundaries for the use of AI in the drafting, execution, and management of contracts, and the legal frameworks governing cross-border healthcare PPPs. This study assists scholarship by establishing a starting point for the administrative law framework of AI in PPPs concerning drafting partnerships in the context of derived services. The balancing of administrative law and the technological innovations of AI to address the incessant demands of the healthcare system aims to advance the administrative laws governing healthcare. The sustainable incorporation of AI in healthcare Public-Private Partnerships (PPPs) is understandable from a technological perspective as well as from an adequate legal perspective that sustains the institutional legitimacy, public accountability, and protection of the patients’ interests.